Interpretasi Ayat-Ayat Korupsi dalam Perpektif Tafsir Al-Azhar Karya Hamka dan Relevansinya Dengan Konteks Modern - Firdaus, Nadya Fitri; Al-Haris, Nizhar Khasyiya Rahman; Bakar, Abu (Sophist : Jurnal Sosial Politik Kajian Islam dan Tafsir, 2025)
One of the social problem issues that is currently being discussed is corruption. The rise of corruption practiced by certain individuals has created new social problems. Because of the complexity of this problem, researchers are interested in making it as anobject of research. In this case, the research will focus on the thematic analysis of corruption in the perspective of tafseer al-Qur'an, especially Tafsir Al-Azhar. The result show that the issue of corruption is discussed quite specifically in the Tafsir Al-Azhar. Meanwhile, the structural-functionalism theory in this research acts as a scalpel which is used as a tool to sharpen the analysis process. This is show Hamka's seriousness in highlighting corruption cases by giving a separate portion of discussion in his tafseer.